Mini Review Immunological Consequences of Immunization With COVID-19 mRNA Vaccines: Preliminary Results - Lombardi, Andrea; Bozzi, Giorgio; Ungaro, Riccardo; Villa, Simone; Castelli, Valeria; Mangioni, Davide; Muscatello, Antonio; Gori, Andrea; Bandera, Alessandra (Frontiers in immunology, 2021)
Background: BNT162b2 and mRNA-1273 are the two recently approved mRNA-based vaccines against COVID-19 which has shown excellent safety and efficacy. Preliminary data about specific and neutralizing antibodies is available covering the first 100 days after vaccination. Methods: We reviewed all the publications regarding the immunologic consequences of BNT162b2 and mRNA-1273 vaccination. A summary of specific antibodies concentration and neutralizing antibodies titers elicited by each vaccine is provided. Results: BNT162b2 and mRNA-1273 displayed a reassuring safety and efficacy profile, with the latter above 94%. They can elicit specific antibodies titers and neutralizing antibodies concentrations that are far superior from those observed among COVID-19 human convalescent serum, across a wide span of age, for at least 100 days after vaccination. Moreover, the vaccine-induced T cellular response is oriented toward a T H 1 response and no evidence of vaccine-enhanced disease have been reported. Discussion: BNT162b2 and mRNA-1273 can elicit specific antibodies titers and neutralizing antibodies concentrations above those observed among COVID-19 human convalescent serum in the first 100 days after vaccination. Data about vaccine efficacy in those with previous COVID-19 or immunocompromised is still limited.